Dielectric materials and functional elements

A Zn-based dielectric material with rare earth elements and Mn achieves ferroelectricity without Mg, addressing composition variability and toxicity issues, ensuring stable and reproducible dielectric performance.

JP7617507B2Active Publication Date: 2025-01-20PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024521590
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-17
Filing Date
2023-03-29
Publication Date
2025-01-20
Estimated Expiration
2043-03-29

AI Technical Summary

Technical Problem

Existing dielectric materials, such as ZnO, require the addition of Mg to exhibit ferroelectricity, which poses challenges in terms of composition variability and potential toxicity from elements like Pb.

Method used

A novel dielectric material comprising Zn, rare earth elements, and Mn is developed, which can exhibit ferroelectricity without the need for Mg, allowing for reduced metal content and improved reproducibility.

Benefits of technology

The novel dielectric material achieves ferroelectricity with reduced metal content, enhancing stability and reducing the use of toxic elements like Pb, while maintaining desired dielectric properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617507000003
    Figure 0007617507000003
  • Figure 0007617507000004
    Figure 0007617507000004
  • Figure 0007617507000005
    Figure 0007617507000005
Patent Text Reader

Abstract

This dielectric material 1a includes a metal oxide having Zn, a rare earth element, and Mn.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to dielectric materials and functional devices. [Background technology]

[0002] Conventionally, materials such as barium titanate BaTiO3, lead zirconate titanate Pb(Zr,Ti)O3, (Pb,La)(Zr,Ti)O3, and BiFO3 are known as dielectric materials having ferroelectricity. (Zr,Ti) means that at least one selected from the group consisting of Zr and Ti is included, and (Pb,La) means that at least one selected from the group consisting of Pb and La is included. These dielectric materials are composite oxides with a perovskite structure.

[0003] On the other hand, in recent years, it has been reported that an oxide in which a part of Zn in ZnO having a wurtzite structure is replaced with a specific element exhibits ferroelectricity. Note that ZnO exhibits paraelectricity. For example, Non-Patent Document 1 states that Zn 1-x Mg x It has been reported that an O thin film exhibits ferroelectricity when x is from 0.34 to 0.37. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] K. Ferri et al, Journal of Applied Physics 130, 044101 (2021) Summary of the Invention [Problem to be solved by the invention]

[0005] The technology described in Non-Patent Document 1 needs to be reconsidered from the viewpoint of expressing predetermined dielectric properties without using Mg as an element for substituting a part of Zn in ZnO. Therefore, the present disclosure provides a novel dielectric material including a metal oxide having Zn and an element other than Mg. [Means for solving the problem]

[0006] The dielectric material of the present disclosure comprises: It contains a metal oxide having Zn, rare earth elements, and Mn. Effect of the Invention

[0007] According to the present disclosure, a novel dielectric material containing Zn and an element other than Mg can be provided. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a cross-sectional view illustrating an example of a dielectric material of the present disclosure. [Diagram 2] FIG. 2 is a diagram illustrating a schematic diagram of another example of the dielectric material of the present disclosure. [Diagram 3] FIG. 3 is a diagram illustrating an example of a functional element according to the present disclosure. [Figure 4] FIG. 4 is an X-ray diffraction (XRD) pattern of the sample according to Example 1. [Diagram 5] FIG. 5 is a graph showing the relationship between polarization and electric field strength in the metal oxide film of the sample according to Example 1. As shown in FIG. [Figure 6] FIG. 6 is a graph showing the relationship between polarization and electric field strength in the metal oxide film of the sample according to Comparative Example 1. As shown in FIG. [Figure 7] FIG. 7 is a graph showing the relationship between polarization and electric field strength in the metal oxide film of the sample according to Comparative Example 2. As shown in FIG. [Figure 8] FIG. 8 is a graph showing the relationship between the composition ratio of Mn and the composition ratio of rare earth elements in the metal oxide samples according to Examples 1 to 8 and Comparative Examples 2 to 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] (Findings on which this disclosure is based) According to Non-Patent Document 1, Zn 1-x Mg x It is understood that when x is 0.34 to 0.37 in the O thin film, the thin film exhibits ferroelectricity. On the other hand, it has not been confirmed that a Zn-containing oxide exhibits predetermined dielectric properties such as ferroelectricity without adding Mg. Therefore, the present inventors have conducted extensive research to determine whether a Zn-containing oxide can exhibit predetermined dielectric properties such as ferroelectricity without adding Mg. As a result, the present inventors have newly discovered that a metal oxide containing Zn and a predetermined metal element other than Mg can exhibit predetermined dielectric properties such as ferroelectricity. Based on this new knowledge, the present inventors have devised the dielectric material of the present disclosure.

[0010] (Summary of one aspect of the present disclosure) The dielectric material according to the first aspect of the present disclosure comprises: It contains a metal oxide having Zn, rare earth elements, and Mn.

[0011] According to the first aspect, the metal oxide contains a rare earth element and Mn in addition to Zn, and exhibits predetermined dielectric properties such as ferroelectricity even if the metal oxide does not contain Mg. Therefore, a novel dielectric material can be provided that contains a metal oxide containing Zn and an element other than Mg.

[0012] In a second aspect of the present disclosure, for example, in the dielectric material according to the first aspect, the metal oxide may have ferroelectricity. According to the second aspect, a novel dielectric material exhibiting ferroelectricity can be provided.

[0013] In a third aspect of the present disclosure, for example, in the dielectric material according to the first or second aspect, the rare earth element may be at least one selected from the group consisting of Nd and Y. According to the third aspect, by using at least one selected from the group consisting of Nd and Y and Mn as elements other than Mg, it is possible to provide a novel dielectric material including a metal oxide having predetermined dielectric properties such as ferroelectricity.

[0014] In a fourth aspect of the present disclosure, for example, in the dielectric material according to the first or second aspect, the rare earth element may be Nd. According to the fourth aspect, by using Nd and Mn as elements other than Mg, a novel dielectric material including a metal oxide having predetermined dielectric properties such as ferroelectricity can be provided.

[0015] In a fifth aspect of the present disclosure, for example, in the dielectric material according to any one of the first to fourth aspects, the metal oxide is Zn 1-x-y A x Mn y O z In the composition, A may be a rare earth element. In the composition, z may be a value for maintaining the electrical neutrality of the metal oxide. The composition may satisfy the conditions of 0.025≦x≦0.05 and 0.7≦y / x≦1.5. According to the fifth aspect, the metal oxide has a predetermined dielectric property such as ferroelectricity even if the rare earth element content and Mn content in the metal oxide are small. Therefore, the content of metal elements other than Zn can be reduced in the metal oxide having the predetermined dielectric property such as ferroelectricity, compared with the case where a part of Zn in ZnO is replaced with Mg to express the predetermined dielectric property such as ferroelectricity.

[0016] In a sixth aspect of the present disclosure, for example, in the dielectric material according to any one of the first to fifth aspects, the metal oxide may have a wurtzite structure. 6 According to an embodiment, the metal oxide tends to have the desired ferroelectric properties.

[0017] In a seventh aspect of the present disclosure, for example, the dielectric material according to any one of the first to sixth aspects may include crystal grains containing the metal oxide, and a filler containing an inorganic oxide different from the metal oxide and filling spaces between the crystal grains. According to the seventh aspect, the dielectric material is likely to have characteristics suitable for a capacitor.

[0018] A functional element according to an eighth aspect of the present disclosure includes: A dielectric material according to any one of the first to seventh aspects; A pair of electrodes.

[0019] According to the eighth aspect, it is possible to provide a functional element making use of the dielectric properties, for example, ferroelectricity, of the metal oxide contained in the dielectric material.

[0020] In the ninth aspect of the present disclosure, for example, the functional element according to the eighth aspect may be at least one selected from the group consisting of a capacitor, an electro-optical element, a memory element, a transistor, a ferroelectric data storage, a piezoelectric element, and a pyroelectric element. According to the ninth aspect, it is possible to provide a functional element such as a capacitor that utilizes the dielectric properties, for example, ferroelectricity, of a metal oxide contained in a dielectric material.

[0021] In a tenth aspect of the present disclosure, for example, the functional element according to the eighth aspect may be disposed in at least one selected from the group consisting of an actuator, an inkjet head, a gyro sensor, a vibration power generating element, a surface acoustic wave resonator, a film bulk resonator, a piezoelectric mirror, and a piezoelectric sensor. According to the tenth aspect, the dielectric properties, for example, ferroelectricity, of the metal oxide contained in the dielectric material can be utilized in the actuator or the like.

[0022] (Embodiment) Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.

[0023] Fig. 1 is a cross-sectional view showing an example of a dielectric material according to the present disclosure. As shown in Fig. 1, the dielectric material 1a is formed, for example, in a film shape. The dielectric material 1a may be formed in a shape other than a film shape, such as a cylindrical shape, a powder shape, or a linear shape.

[0024] The dielectric material 1a contains a metal oxide having Zn, a rare earth element, and Mn. This metal oxide does not contain, for example, Mg. The metal oxide has a predetermined dielectric property such as ferroelectricity even if it does not contain Mg. This metal oxide may contain Mg as necessary. It is considered that the metal oxide containing Zn, a rare earth element, and Mn makes it easier to form a crystal of the metal oxide so that spontaneous polarization occurs. For example, it is considered that the dimension of the unit cell of the crystal in the c-axis direction is easier to become large.

[0025] In the dielectric material 1a, the dielectric properties of the metal oxide are not limited to a specific one, and the metal oxide contained in the dielectric material 1a may have, for example, ferroelectricity.

[0026] The above metal oxides can have predetermined dielectric properties such as ferroelectricity even if the content of metal elements other than Zn in the metal oxide is small. Therefore, the variation in composition and crystal structure in the metal oxide is small, and the above metal oxides are advantageous in terms of reproducibility. In addition, the spontaneous polarization of the metal oxides is likely to be large even if the metal oxides do not contain toxic elements such as Pb.

[0027] The rare earth element in the metal oxide is not limited to a specific rare earth element. The rare earth element in the metal oxide is, for example, at least one selected from the group consisting of Nd and Y. This makes it easier for the metal oxide to have the desired ferroelectricity. The rare earth element in the metal oxide may be an element other than Nd and Y. The ionic radii of the ions derived from the rare earth elements are close to each other as shown in Table 1. Therefore, even if the rare earth element in the metal oxide is an element other than Nd and Y, it is considered that the crystal of the metal oxide is easily formed so that spontaneous polarization occurs. The rare earth element in the metal oxide may be at least one selected from the group consisting of Y, La, Ce, Pr, and Nd. The ionic radii in Table 1 are Shannon's ionic radii reported in RD Shannon, Acta Crystallogr. Sect. A, 32, 751 (1976).

[0028] [Table 1]

[0029] The rare earth element in the metal oxide is preferably Nd, which makes it easier for the metal oxide to have the desired ferroelectricity.

[0030] The composition of the metal oxide is not limited to a specific composition as long as the metal oxide has Zn, a rare earth element, and Mn. 1-x-y A x Mn y O zIn this composition, A is a rare earth element, and z is a value for maintaining the electrical neutrality of the metal oxide. This composition satisfies the conditions of 0.025≦x≦0.05 and 0.7≦y / x≦1.5. When the metal oxide has such a composition, even if the content of rare earth elements and the content of Mn in the metal oxide are small, the metal oxide has a predetermined dielectric property such as ferroelectricity. Compared to the case where a part of Zn in ZnO is replaced with Mg to express the predetermined dielectric property such as ferroelectricity, the content of metal elements other than Zn can be reduced in the metal oxide having the predetermined dielectric property such as ferroelectricity.

[0031] In the above composition, z can vary depending on the contents of the rare earth element A and Mn, and the manufacturing process of the dielectric material 1a. For example, z satisfies the condition 0.9≦z≦1.1.

[0032] The crystal structure of the metal oxide is not limited to a specific crystal structure, as long as the metal oxide has Zn, rare earth elements, and Mn. The metal oxide has, for example, a wurtzite structure. In this case, the metal oxide is likely to have the desired ferroelectricity. For example, the remanent polarization is likely to be large in the metal oxide.

[0033] The dielectric material 1a is, for example, configured as a material consisting of only a metal oxide. The dielectric material 1a may be configured as a composite material containing a metal oxide. FIG. 2 is a diagram showing a schematic diagram of another example of the dielectric material of the present disclosure. The dielectric material 1a may be, for example, modified to the dielectric material 1b shown in FIG. 2.

[0034] The method for producing the dielectric material 1a is not limited to a specific method. The dielectric material 1a can be produced by a vacuum process such as RF magnetron sputtering, pulsed laser deposition (PLD), atomic layer deposition (ALD), and chemical vapor deposition (CVD). The dielectric material 1a can also be produced by a wet process such as chemical solution deposition (CSD), sol-gel, and hydrothermal.

[0035] As shown in Fig. 2, the dielectric material 1b includes crystal grains 1g and a filler 1f. The crystal grains 1g contain the above-mentioned metal oxide. The filler 1f contains an inorganic oxide different from the above-mentioned metal oxide, and fills the spaces between the crystal grains 1g. With this configuration, the dielectric material 1b is likely to have characteristics suitable for a capacitor.

[0036] The method for producing the dielectric material 1b is not limited to a specific method. The dielectric material 1b is produced, for example, by the following method. First, a powder containing the above-mentioned metal oxide raw material and the raw material of the filler 1f is mixed with a binder to obtain a mixture. This mixture is formed into a sheet by a method such as screen printing to obtain a green sheet. The dielectric material 1b can be produced by firing this green sheet.

[0037] A specific functional element can be provided using the dielectric material 1a or 1b. FIG. 3 is a diagram showing a schematic diagram of an example of a functional element according to the present disclosure. As shown in FIG. 3, the functional element 2 includes, for example, a dielectric 10 and a pair of electrodes 20. The dielectric 10 includes the dielectric material 1a. The dielectric 10 may include the dielectric material 1b. Since the functional element 2 includes the dielectric 10, it can be used in applications that utilize the dielectric properties, such as ferroelectricity, of the metal oxide included in the dielectric material 1a of the dielectric 10.

[0038] As shown in FIG. 3, in the functional element 2, the dielectric 10 is disposed between a pair of electrodes 20, for example.

[0039] The functional element 2 is not limited to a specific element. The functional element 2 is, for example, at least one selected from the group consisting of a capacitor, an electro-optical element, a memory element, a transistor, a ferroelectric data storage, a piezoelectric element, and a pyroelectric element. For example, in these functional elements, the dielectric properties, such as ferroelectricity, of the metal oxide contained in the dielectric material 1a of the dielectric 10 can be utilized.

[0040] The functional element 2 is disposed in at least one selected from the group consisting of, for example, an actuator, an inkjet head, a gyro sensor, a vibration power generating element, a surface acoustic wave resonator, a film bulk resonator, a piezoelectric mirror, and a piezoelectric sensor. In this case, the actuator or the like can utilize the piezoelectric effect associated with the dielectric properties of the metal oxide contained in the dielectric material 1a of the dielectric 10. EXAMPLES

[0041] The present disclosure will be described in more detail below based on examples, although the present disclosure is not limited to the following examples.

[0042] Example 1 A Pt(111) film having a thickness of 100 nm was epitaxially grown on a c-plane sapphire single crystal substrate by RF magnetron sputtering to obtain a Pt electrode. Next, a metal oxide film having a thickness of 200 nm was formed on the Pt electrode by RF magnetron sputtering. The metal oxide film contained Zn, Nd, and Mn as metals. In the metal oxide film, the ratio of the number of Nd atoms to the number (total number) of Zn, Nd, and Mn atoms was 0.045. In the metal oxide film, the ratio of the number of Mn atoms to the number (total number) of Zn, Nd, and Mn atoms was 0.042. In this RF magnetron sputtering, a composite oxide containing Zn, Nd, and Mn was used as a target. In this target, the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1: 0.87: 0.05 was satisfied. In addition, in this RF magnetron sputtering, the Pt electrode was heated to 300°C in an atmosphere containing a mixture of 25% oxygen and argon by volume. Next, a 100 nm thick Au film was formed on the metal oxide film by vacuum deposition to obtain an Au electrode. In this way, a sample according to Example 1 was obtained.

[0043] The crystal structure of the metal oxide film of the sample according to Example 1 was evaluated using an X-ray diffraction (XRD) device X'Pert Pro MPD manufactured by Panalytical. In the XRD, Cu-Kα radiation (wavelength λ=0.15418 nm) was used as the X-ray. FIG. 4 shows the XRD pattern of the sample according to Example 1. According to FIG. 4, in addition to the diffraction peak derived from the substrate, the diffraction peak of the (00L) plane of the wurtzite structure appears with high intensity. Therefore, it was confirmed that the metal oxide film in the sample according to Example 1 has a wurtzite structure, and that the metal oxide film has grown epitaxially so that the c-plane of the wurtzite structure is parallel to the substrate.

[0044] The composition of the metal oxide film of the sample according to Example 1 was determined using an X-ray photoelectron spectroscopy (XPS) analyzer ESCA5600 manufactured by ULVAC-PHI, Inc. The ratio x of the number of rare earth element atoms to the total number of Zn atoms, rare earth element atoms, and Mn atoms in the metal oxide film, and the ratio y of the number of Mn atoms to the total number are shown in Table 1. 2 As shown in.

[0045] A polarization-electric field measurement was performed on the sample according to Example 1 using a ferroelectric tester Premier II manufactured by Radiant Technology, and a PE curve of the sample according to Example 1 was obtained. The dielectric properties of the metal oxide of the sample according to Example 1 were evaluated based on this PE curve. The results are shown in Table 1. 2 Table 2 In the above, an electrical insulation rating of "A" means that the metal oxide has good electrical insulation. An electrical insulation rating of "X" means that the metal oxide exhibits electrical conductivity. A ferroelectric rating of "A" means that the metal oxide exhibits ferroelectricity. A ferroelectric rating of "X" means that the metal oxide does not have ferroelectricity. It was confirmed that the metal oxide film of the sample according to Example 1 has good electrical insulation and is a ferroelectric material exhibiting high polarization.

[0046] 5 is a PE curve of the sample according to Example 1, showing the relationship between polarization and electric field strength in the metal oxide film. In Fig. 5, the vertical axis shows polarization, and the horizontal axis shows electric field strength. As shown in Fig. 5, the metal oxide film of the sample according to Example 1 has a polarization of about 130 μC / cm 2 It was confirmed that the metal oxide film was a ferroelectric material exhibiting high polarization.

[0047] Example 2 A sample according to Example 2 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1:0.53:0.05 was satisfied. The crystal structure of the metal oxide film of the sample according to Example 2 was evaluated in the same manner as in Example 1. As a result, it was confirmed that the metal oxide film in the sample according to Example 2 has a wurtzite structure, and that the metal oxide film has grown epitaxially so that the c-plane of the wurtzite structure is parallel to the substrate. The composition of the metal oxide film of the sample according to Example 2 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Example 2 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 It was confirmed that the metal oxide film of the sample according to Example 2 had good electrical insulation properties and was a ferroelectric material exhibiting high polarization.

[0048] Example 3 A sample according to Example 3 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of Zn atomic number:Nd atomic number:Mn atomic number=1:0.053:0.04 was satisfied. The crystal structure of the metal oxide film of the sample according to Example 3 was evaluated in the same manner as in Example 1. As a result, it was confirmed that the metal oxide film in the sample according to Example 3 has a wurtzite structure, and that the metal oxide film has grown epitaxially so that the c-plane of the wurtzite structure is parallel to the substrate. The composition of the metal oxide film of the sample according to Example 3 was determined in the same manner as in Example 1. The results are shown in Table 1. 2The dielectric properties of the metal oxide film of the sample according to Example 3 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 It was confirmed that the metal oxide film of the sample according to Example 3 had good electrical insulation properties and was a ferroelectric material exhibiting high polarization.

[0049] Example 4 A sample according to Example 4 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1:0.087:0.04 was satisfied. The crystal structure of the metal oxide film of the sample according to Example 4 was evaluated in the same manner as in Example 1. As a result, it was confirmed that the metal oxide film in the sample according to Example 4 has a wurtzite structure, and that the metal oxide film has grown epitaxially so that the c-plane of the wurtzite structure is parallel to the substrate. The composition of the metal oxide film of the sample according to Example 4 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Example 4 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 It was confirmed that the metal oxide film of the sample according to Example 4 was a ferroelectric material having good electrical insulation properties and exhibiting high polarization.

[0050] Example 5 A sample according to Example 5 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1:0.087:0.07 was satisfied. The crystal structure of the metal oxide film of the sample according to Example 5 was evaluated in the same manner as in Example 1. As a result, it was confirmed that the metal oxide film in the sample according to Example 5 has a wurtzite structure, and that the metal oxide film has grown epitaxially so that the c-plane of the wurtzite structure is parallel to the substrate. The composition of the metal oxide film of the sample according to Example 5 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Example 5 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2It was confirmed that the metal oxide film of the sample according to Example 5 had good electrical insulation properties and was a ferroelectric material exhibiting high polarization.

[0051] Example 6 A sample according to Example 6 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1:0.087:0.08 was satisfied. The crystal structure of the metal oxide film of the sample according to Example 6 was evaluated in the same manner as in Example 1. As a result, it was confirmed that the metal oxide film in the sample according to Example 6 has a wurtzite structure, and that the metal oxide film has grown epitaxially so that the c-plane of the wurtzite structure is parallel to the substrate. The composition of the metal oxide film of the sample according to Example 6 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Example 6 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 It was confirmed that the metal oxide film of the sample according to Example 6 was a ferroelectric material having good electrical insulation properties and exhibiting high polarization.

[0052] Example 7 A sample according to Example 7 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1:0.053:0.03 was satisfied. The crystal structure of the metal oxide film of the sample according to Example 7 was evaluated in the same manner as in Example 1. As a result, it was confirmed that the metal oxide film in the sample according to Example 7 has a wurtzite structure, and that the metal oxide film has grown epitaxially so that the c-plane of the wurtzite structure is parallel to the substrate. The composition of the metal oxide film of the sample according to Example 7 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Example 7 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 It was confirmed that the metal oxide film of the sample according to Example 7 was a ferroelectric material having good electrical insulation properties and exhibiting high polarization.

[0053] Example 8 A sample according to Example 8 was produced in the same manner as in Example 1, except for the following points. The composite oxide target contained Y instead of Nd as a rare earth element, and satisfied the condition of Zn atomic number:Y atomic number:Mn atomic number=1:0.075:0.05. The crystal structure of the metal oxide film of the sample according to Example 8 was evaluated in the same manner as in Example 1. As a result, it was confirmed that the metal oxide film in the sample according to Example 8 had a wurtzite structure, and that the metal oxide film had grown epitaxially so that the c-plane of the wurtzite structure was parallel to the substrate. The composition of the metal oxide film of the sample according to Example 8 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Example 8 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 It was confirmed that the metal oxide film of the sample according to Example 8 was a ferroelectric material having good electrical insulation properties and exhibiting high polarization.

[0054] Comparative Example 1 A sample according to Comparative Example 1 was produced in the same manner as in Example 1, except for the following points. The composite oxide target contained Mg without containing rare earth elements, and satisfied the condition of Zn atomic number:Mg atomic number:Mn atomic number=1:0.55:0.02. The dielectric properties of the metal oxide film of the sample according to Comparative Example 1 were evaluated in the same manner as in Example 1. The results are shown below. 2 6 is a graph showing the relationship between polarization and electric field strength in the metal oxide film of the sample according to Comparative Example 1. As shown in FIG. 6, the metal oxide film of the sample according to Comparative Example 1 had good electrical insulation properties, but had paraelectric dielectric properties and was not a ferroelectric.

[0055] Comparative Example 2 A sample according to Comparative Example 2 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of Zn atomic number: Nd atomic number: Mn atomic number = 1: 0.053: 0.02 was satisfied. The composition of the metal oxide film of the sample according to Comparative Example 2 was determined in the same manner as in Example 1. The results are shown in Table 1.2 The dielectric properties of the metal oxide film of the sample according to Comparative Example 2 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 7 is a graph showing the relationship between polarization and electric field strength in the metal oxide film of the sample according to Comparative Example 2. As shown in FIG. 7, the metal oxide film of the sample according to Comparative Example 2 exhibited electrical conductivity, and a large current leak was observed in the measurement for obtaining the PE curve.

[0056] Comparative Example 3 A sample according to Comparative Example 3 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1: 0.087: 0.03 was satisfied. The composition of the metal oxide film of the sample according to Comparative Example 3 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Comparative Example 3 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 The metal oxide film of the sample according to Comparative Example 3 exhibited electrical conductivity, and a large current leak was observed in the measurement for obtaining the PE curve.

[0057] Comparative Example 4 A sample according to Comparative Example 4 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1:0.031:0.03 was satisfied. The composition of the metal oxide film of the sample according to Comparative Example 4 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Comparative Example 4 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 The metal oxide film of the sample according to Comparative Example 4 exhibited electrical conductivity, and a large current leak was observed in the measurement for obtaining the PE curve.

[0058] Comparative Example 5 A sample according to Comparative Example 5 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1:0.031:0.04 was satisfied. The composition of the metal oxide film of the sample according to Comparative Example 5 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Comparative Example 5 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 The metal oxide film of the sample according to Comparative Example 5 exhibited electrical conductivity, and a large current leak was observed in the measurement for obtaining the PE curve.

[0059] Comparative Example 6 A sample according to Comparative Example 6 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1:0.031:0.05 was satisfied. The composition of the metal oxide film of the sample according to Comparative Example 6 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Comparative Example 6 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 The metal oxide film of the sample according to Comparative Example 6 exhibited electrical conductivity, and a large current leak was observed in the measurement for obtaining the PE curve.

[0060] Comparative Example 7 A sample according to Comparative Example 7 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1: 0.053: 0.06 was satisfied. The composition of the metal oxide film of the sample according to Comparative Example 7 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Comparative Example 7 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 The metal oxide film of the sample according to Comparative Example 7 exhibited electrical conductivity, and a large current leak was observed in the measurement for obtaining the PE curve.

[0061] Comparative Example 8 A sample according to Comparative Example 8 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1: 0.053: 0.07 was satisfied. The composition of the metal oxide film of the sample according to Comparative Example 8 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Comparative Example 8 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 The metal oxide film of the sample according to Comparative Example 8 exhibited low electrical insulation and electrical conductivity, and a large current leak was observed in the measurement for obtaining a PE curve.

[0062] Comparative Example 9 A sample according to Comparative Example 9 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1: 0.11: 0.07 was satisfied. The composition of the metal oxide film of the sample according to Comparative Example 9 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Comparative Example 9 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 The metal oxide film of the sample according to Comparative Example 9 exhibited low electrical insulation and electrical conductivity, and a large current leak was observed in the measurement for obtaining a PE curve.

[0063] Comparative Example 10 A sample according to Comparative Example 10 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1: 0.11: 0.05 was satisfied. The composition of the metal oxide film of the sample according to Comparative Example 10 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Comparative Example 10 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 The metal oxide film of the sample according to Comparative Example 10 exhibited low electrical insulation and electrical conductivity, and a large current leak was observed in the measurement for obtaining a PE curve.

[0064] Comparative Example 11 A sample according to Comparative Example 11 was produced in the same manner as in Example 1, except that the composite oxide target was changed so that the condition of the number of Zn atoms: the number of Nd atoms: the number of Mn atoms = 1: 0.087: 0.1 was satisfied. The composition of the metal oxide film of the sample according to Comparative Example 11 was determined in the same manner as in Example 1. The results are shown in Table 1. 2 The dielectric properties of the metal oxide film of the sample according to Comparative Example 11 were evaluated in the same manner as in Example 1. The results are shown in Table 1. 2 The metal oxide film of the sample according to Comparative Example 11 exhibited low electrical insulation and electrical conductivity, and a large current leak was observed in the measurement for obtaining a PE curve.

[0065] 8 is a graph showing the relationship between the composition ratio y of Mn and the composition ratio x of rare earth elements in the metal oxide samples according to Examples 1 to 8 and Comparative Examples 2 to 11. In this graph, "◯" indicates an Example and "×" indicates a Comparative Example. As shown in FIG. 8, the metal oxide samples according to Examples 1 to 8 satisfied the conditions of 0.025≦x≦0.05 and 0.7≦y / x≦1.5. On the other hand, the metal oxide samples according to Comparative Examples 2 to 11 did not satisfy at least one of 0.025≦x≦0.05 and 0.7≦y / x≦1.5.

[0066] [Table 2] [Industrial Applicability]

[0067] The dielectric material of the present disclosure can have predetermined dielectric properties, such as ferroelectricity, even without using Mg as an element to substitute for a portion of Zn in ZnO.

Claims

1. A metal oxide having Zn, a rare earth element, and Mn, The metal oxide has a composition represented by Zn1-xyAxMnyOz, In the above composition, A is a rare earth element; In the above composition, z is a value for maintaining the electrical neutrality of the metal oxide, The composition satisfies the conditions of 0.025≦x≦0.05 and 0.7≦y / x≦1.5, Dielectric materials.

2. The metal oxide has ferroelectric properties. The dielectric material of claim 1 .

3. The rare earth element is at least one selected from the group consisting of Nd and Y. The dielectric material of claim 1 .

4. The rare earth element is Nd. The dielectric material of claim 1 .

5. The metal oxide has a wurtzite structure. The dielectric material of claim 1 .

6. The dielectric material includes crystal grains containing the metal oxide, and a filler containing an inorganic oxide different from the metal oxide and filling spaces between the crystal grains. The dielectric material of claim 1 .

7. A dielectric material comprising the dielectric material according to any one of claims 1 to 6; A pair of electrodes; Functional element.

8. The functional element is at least one selected from the group consisting of a capacitor, an electro-optical element, a memory element, a transistor, a ferroelectric data storage, a piezoelectric element, and a pyroelectric element. The functional element according to claim 7 .

9. the functional element is disposed in at least one selected from the group consisting of an actuator, an inkjet head, a gyro sensor, a vibration power generating element, a surface acoustic wave resonator, a film bulk resonator, a piezoelectric mirror, and a piezoelectric sensor; The functional element according to claim 7 .

Citation Information

Patent Citations

  • Ferroelectric ceramics

    JP1989298063A

  • Cr composite component

    JP1994333781A